2019
DOI: 10.1007/s00300-019-02578-1
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response to irradiance, temperature and co-cultivation in Antarctic engineering brown algae (Desmarestia menziesii and D. anceps)

Abstract: The Western Antarctic Peninsula (WAP) is a hot spot of global warming, including decreased sea-ice cover during winter and increased sedimentation during summer due to glacial melt. Subsequently, an altered irradiance and temperature regime in the water column may affect the performance of primary producers and change competitive structures. The brown, subtidal macroalgae Desmarestia menziesii and D. anceps are ecosystem engineers and of extreme importance for the Antarctic coastal ecosystem. Individuals of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 69 publications
(112 reference statements)
1
4
0
Order By: Relevance
“…As growth was optimal at 0-5 °C, D. menziesii otherwise is in line with other endemic Antarctic Desmarestiales (Wiencke and tom Dieck 1989Dieck , 1990Zacher et al 2016;Savaglia et al 2019) showing a specific cold-water adapted growth response. At higher temperatures growth and maximum photosynthetic quantum yield F v /F m of sporophytes constantly decreased over a period of 14 days, reaching lowest values at 15 and 16 °C.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…As growth was optimal at 0-5 °C, D. menziesii otherwise is in line with other endemic Antarctic Desmarestiales (Wiencke and tom Dieck 1989Dieck , 1990Zacher et al 2016;Savaglia et al 2019) showing a specific cold-water adapted growth response. At higher temperatures growth and maximum photosynthetic quantum yield F v /F m of sporophytes constantly decreased over a period of 14 days, reaching lowest values at 15 and 16 °C.…”
Section: Discussionsupporting
confidence: 78%
“…photosynthesis in macroalgae (Navarro et al 2020) and F v /F m has been successfully used to quantify detrimental responses to temperature as an early warning indicator rather than thallus bleaching, especially at upper sub-lethal temperatures (Olabarria et al 2013;Graiff et al 2015;Savaglia et al 2019). Prior to the beginning of the acclimation phase (day -6), pre-experimental individuals were measured to document the initial status of the material after cultivation (n = 4).…”
Section: Maximum Quantum Yield (F V /F M ) Of the Sporophytesmentioning
confidence: 99%
See 1 more Smart Citation
“…requirement for growth in L. glaciale rhodoliths lowers, and/or rhodoliths utilize stored photosynthates, at near-zero temperatures. Savaglia et al (2019) found that photosynthetic efficiency of the Antarctic phaeophytes Desmarestia menziesii and D. anceps was higher at 2°C with low irradiance (10 μmol pho-tonsÁm −2 Ás −1 ) than 7°C with high irradiance (100 μmol photonsÁm −2 Ás −1 ) conditions. Schwarz et al (2005) found a light compensation point of ~0.1 µmol photonsÁm -2 Ás -1 in Antarctic coralline algae crusts exposed to low-light conditions under sea ice over ~17 months.…”
Section: Discussionmentioning
confidence: 91%
“…Savaglia et al. (2019) found that photosynthetic efficiency of the Antarctic phaeophytes Desmarestia menziesii and D. anceps was higher at 2°C with low irradiance (10 μmol photons·m −2 ·s −1 ) than 7°C with high irradiance (100 μmol photons·m −2 ·s −1 ) conditions. Schwarz et al.…”
Section: Discussionmentioning
confidence: 99%